2013
DOI: 10.1038/eye.2013.51
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene vs silicone Ahmed valve with adjunctive mitomycin C in paediatric age group: a prospective controlled study

Abstract: Purpose To compare the results of silicone and polypropylene Ahmed glaucoma valves (AGV) implanted during the first 10 years of life. Methods A prospective study was performed on 50 eyes of 33 patients with paediatric glaucoma. Eyes were matched to either polypropylene or silicone AGV. In eyes with bilateral glaucoma, one eye was implanted with polypropylene and the other eye was implanted with silicone AGV. Results Fifty eyes of 33 children were reviewed. Twenty five eyes received a polypropylene valve, and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…In contrast, previous studies in adult eyes comparing silicone and polypropylene GDDs suggested similar, if not better, success rates with silicone GDDs. [14][15][16][17] To our knowledge, comparisons between AGVs in pediatric patients are limited to 2 studies, which showed better survival with silicone valves. 16,17 Although silicone GDDs were implanted at an earlier age than polypropylene GDDs, age was not a risk factor in the silicone GDD subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, previous studies in adult eyes comparing silicone and polypropylene GDDs suggested similar, if not better, success rates with silicone GDDs. [14][15][16][17] To our knowledge, comparisons between AGVs in pediatric patients are limited to 2 studies, which showed better survival with silicone valves. 16,17 Although silicone GDDs were implanted at an earlier age than polypropylene GDDs, age was not a risk factor in the silicone GDD subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…The Ahmed valve and other GDDs have also been proved valid and effective options in the management of pediatric glaucoma, both with AC and posterior segment placement of the tube 44, 45, 46, 47, 48, 49, 50, 51, 52. We are aware that data extrapolation from our two cases of PC8 model implantation is not possible.…”
Section: Discussionmentioning
confidence: 98%
“…Apart from the differences in the ligation methods, the slightly higher incidence of hypotony in our study may be related to differences in the material properties of the AGV (S2 model in previous studies and FP7 here) because the silicone plate tended to have more postoperative hypotony (statistically insignificant). [15][16][17] However, it seems that partial ligation methods can reduce hypotony-related complications. In this and previous reports using partial ligation in AGV surgery, hypotony-related complications did not require surgical interventions.…”
Section: Discussionmentioning
confidence: 99%